Stability and function of adult vasculature is sustained by Akt/Jagged1 signalling axis in endothelium - Bethany A. Kerr (Nature Portfolio, 2016)
The Akt pathway integrates multiple signals, but whether it affects vasculature function is debatable. Here the authors show that Akt pathway shutdown in adult mouse endothelium causes destabilization of vasculature leading to cardiac and retinal dysfunction, due to decreased levels of Jagged1 and impaired Notch signaling.